Weil’s disease with multiple organ dysfunction, community-acquired pneumonia and septic shock: The role of rapid diagnosis and management - Hermawati, Berty D.; Hapsari, Brigitta DA.; Wulandari, Evi L.; Prabowo, Nurhasan A.; Sukmagautama, Coana; Putri, Desy P.; Apriningsih, Hendrastutik; Rahma, Annisa A.; Nafila, Ragil R. (Narra Sains Indonesia, 2024)
Leptospirosis is an uncommon infectious illness – a spirochetal zoonosis – caused by Leptospira species and the primary cause of human leptospirosis is exposure to the urine of infected rodents. Clinical manifestations of human leptospirosis are diverse, ranging from asymptomatic infection to severe life-threatening with multiorgan dysfunction. The severe condition is known as Weil's disease, which is characterized by feverish illness with jaundice, acute kidney damage, and bleeding. The aim of this case report was to present a Weil's disease which occurred simultaneously with a community-acquired pneumonia (CAP) resulting in serious complications. A 41-year-old man with Weil's disease, as well as CAP caused by Streptococcus pneumoniae, and septic shock was presented. The patient was treated accordingly after establishing the diagnosis through history taking, physical examination, and laboratory tests. In this instance, the score for diagnosing leptospirosis based on Modified Faine's Criteria was calculated resulting possible diagnoses; and therefore, therapeutic management was initiated. Despite presenting with severe symptoms, the patient recovered completely after receiving antibiotics and supportive care. This study highlights that when a patient has Weil’s disease and a CAP infection, which could cause unfavorable consequence, a prompt diagnosis and proper treatment could result satisfied patient recovery.